Ultrasonic dispersal of buckminster fullerene [c60] leads to the formation of [8-hydroxy]fullerenol : synthesis and application - Afreen, Sadia (2018)
This thesis is focused on investigating the possibility of synthesizing polyhydroxylated fullerene/fullerenol from the ultrasonic dispersal of Buckminster fullerene (C60). Interestingly, ultrasonic dispersion of fullerene may result into potential fullerenol moieties, the prospect of which has long been overlooked to date and unnoted by others, hence it lacks quantitative analysis in explaining the possibility. On this context, based on some of the established facts, this thesis is going to evidence the possibility that when pristine fullerene is dispersed in an aqueous medium by ultrasonication, the acoustic cavitation resulting from sonication orchestrates the hydroxylation of fullerene to fullerenol moieties instead of hydration of fullerene molecules in the aqueous medium. This thesis deals with the above-raised possibility with a series of analytical studies and quantitative analysis which ultimately has proven that potential fullerenol moieties could be synthesized by the technique of ultrasonication, and this thesis is first to report that the most possible molecular structure of the potential fullerenol to be synthesized is C60(OH)8.2H2O with a yield up to 4.0%.